Learning speaking through dialogue task-based learning approach in physiotherapy department - Noerdjanah, Noerdjanah; Khomarun, Khomarun; Sugiono, Sugiono (ARKA INSTITUTE, 2025)
The ability to speak in English is an important skill for vocational students, especially in the Department of Physiotherapy of the Poltekkes Kemenkes Surakarta, considering the need for professional communication with patients and other medical personnel. However, there are still many students who have difficulty speaking actively and confidently. The purpose of this study is to ascertain how well students' speaking abilities are improved by the dialogue task-based learning technique. Using the Wilcoxon Signed-Rank test in a pretest-posttest design, a quantitative research methodology was employed. For one semester, 110 students who engaged in dialogue-based task-based learning made up the research sample. The Wilcoxon test results revealed a significant difference between the pretest and posttest scores, with a significance value of 0.000 (p < 0.05) and an increase in scores for all responders. In the context of health vocational education, it can be inferred that the dialogue task-based learning technique is successful in enhancing students' speaking abilities.